PENINGKATAN HASIL BELAJAR KOGNITIF SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DI KELAS X SMK TARUNA SATRIA PEKANBARU - Aulia Ramadhani; Azhar Azhar; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the improvement of the learning outcomes cognitive science of physics by using Cooperative Integrated Reading and Composition (CIRC) learning model. This research was conducted in SMK Taruna Satria Pekanbaru from July to October 2019. The subjects were students of class X TKJ4 was 28 students consisting of 20 male students and 8 female students. The research metodh is pre-experimental with One Group Pretest-Posttest Design. The instrument of data collection in this research is a cognitive achievement test consists of 15 multiple choice items. The analysis of the data in this research is a descriptive analysis. The descriptive analysis were obtained an average score of students before treatment by 41.67, after being given treatment, the average score of students was 80.24. Gain calculation shows that cognitive learning outcomes of students has increased by 0.66 with the medium category. Thus it can be concluded that the use of Cooperative Integrated Reading and Composition learning model can improve cognitive learning outcomes of students of class X SMK Taruna Satria Pekanbaru in the subject matter motion and force.Key Words: Cognitive Learning Outcomes, Cooperative Integrated Reading And Composition, Motion and Force